2018
DOI: 10.24275/uam/izt/dcbi/revmexingquim/2019v18n3/torres
|View full text |Cite
|
Sign up to set email alerts
|

Effect on Discoloration by Nonthermal Plasma in Dissolved Textile Dyes: Acid Black 194

Abstract: Modelado de la biodegradación en biorreactores de lodos de hidrocarburos totales del petróleo intemperizados en suelos y sedimentos (Biodegradation modeling of sludge bioreactors of total petroleum hydrocarbons weathering in soil and sediments)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Water pollution caused by factories discharging large volumes of wastewater containing colorants (textiles, food, paper, plastics, among others) is a significant problem (Crini & Badot, 2008;Torres-Segundo et al, 2019;Márquez-Rámirez & Michtchenco, 2019). Even though these effluents contain small amounts of dye (less than 10 mg/L), they cause water coloring (No & Meyers, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Water pollution caused by factories discharging large volumes of wastewater containing colorants (textiles, food, paper, plastics, among others) is a significant problem (Crini & Badot, 2008;Torres-Segundo et al, 2019;Márquez-Rámirez & Michtchenco, 2019). Even though these effluents contain small amounts of dye (less than 10 mg/L), they cause water coloring (No & Meyers, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Once the secondary microorganism treatment is finished, the effluent can pass to a tertiary treatment to further improve the quality. Advanced oxidation processes (AOPs) are among the current successful technologies evaluated (Harrelkas et al, 2008;Zangeneh et al 2015;Torres-Segundo et al, 2019;Suarez-Vázquez et al, 2019). In general, AOPs are defined as a set of physico-chemical processes specifically designed to generate reactive oxidative species, such as (OH * ) that concomitantly help with in situ oxidation processes.…”
Section: Introductionmentioning
confidence: 99%
“…In studying flax yarns treated with O 2 plasma,Seghini et al (2019) observed a similar stretching band at 1741 cm −1 that they attributed to the formation of carbonyl and carboxyl species. Air plasma contains O 2 -based reactive species like O 2• and HO • (N 2 is less reactive than O 2 ) according to the following reactions: O 2 + e − → 2O 2• + e − and H 2 O + γ UV or e − → 2HO • + 2H • (deFarias et al, 2017;Acayanka et al, 2019;Thirumdas et al, 2015;Brisset and Pawlat, 2016;Torres-Segundo et al, 2019). Air plasma also contains e − and γ UV .…”
mentioning
confidence: 99%